Pengaruh Manajemen Mutu ISO 9001:2015 dan Motivasi Terhadap Kinerja Karyawan Pada Kantor PT. Kereta Api Indonesia (Persero) Daerah Operasi IX Unit Kerja Jember - Hendra Gunawan; M. Syarif Hidayatullah Elmas (Ecobuss, 2017)
This research was done at the Office of PT. Kereta Api Indonesia(Persero) Daerah Operasi IXUnit Kerja Jember with the aim to know the quality management ISO 9001:2015 and motivation climate simultaneously, partial, and dominant against the performance employee at the Office of PT. Kereta Api Indonesia (Persero) Daerah Operasi IX Unit Kerja Jember. The research’s type that is used is a quantitative research with the approach of descriptive data analysis, research that many use numbers, starting from data collection, data interpretation, and the result are described by descriptive. Data collection technique that is used is the questionnaire, interview, and documentation. The samples in this research are as much as 100 people from 134 employees remain at the Office of PT. Kereta Api Indonesia (Persero) Daerah Operasi IX Unit Kerja Jember using Proportional Stratified Random Sampling and the samples determination technique using the test of the data adequacy according to the Slovin’s formula. Data analysis used are the data quality analysis, classical assumptions analysis, determination coefficient analysis and multiple regression analysis with SPSS 20. The results of the research showed that: 1) based on the test results significant simultaneous/together produce a 1029,573 Fcount while Ftabel value on equal trust 95% is 3.09. Thus Fcount (1029,573) consecutive patients Ftabel (3.09) can be said that there is a significant influence simultaneously between the quality management 9001:2015 (X1) and motivation (X2) against the performance employee at the Office of PT. Kereta Api Indonesia (Persero) Daerah Operasi IX Unit Kerja Jember; 2) based on the test results t partial variables X1 and X2 against the variables Y obtained count value quality management 9001:2015 variables (X1) of 21,289 and motivation (X2) of 11,019 while ttable on equal trust 95% is 1.66 thus thitung (21,289) and (11,019) > table (1,66) quality management 9001:2015 affect the dominant against the performance employee at the Office PT. Kereta Api Indonesia (Persero) Daerah Operasi IX Unit Kerja Jember. Based on the results of the above analysis it can be concluded that there is a significant influence partially between the quality management 9001:2015 (X1) and motivation (X2) against the performance employee at the Office PT. Kereta Api Indonesia (Persero) Daerah Operasi IX Unit Kerja Jember. Key Words: Quality Management 9001:2015, Motivation, PT. KAI DAOP IX Jember, and Performance Employee